Caracterização morfoagronômica e química de acessos de coqueiro-anão e coqueiro-gigante - Sobral, Kamila Marcelino Brito (2017)
The genetic variability of the species Cocos nucifera L. that existing in Brazil is conserved in the International Coconut Germplasm Bank for Latin America and Caribe (ICG-LAC), which is located in the counties of Neopolis and Itaporanga d´Ajuda in the state of Sergipe, Brazil. Since from the establishment of the ICG-LAC some studies were carried out. However, this germplasm needs to be studied in depth comprising the morphoagronomical characterization, chemical and molecular evaluation in order to allow to estimate the genetic variability of the accessions. Thus, the aim of this work was to characterize morphologically coconut accessions (dwarfs and talls). The trials were carried out with eight tall coconut accessions in one cycle of production using 34 quantitative descriptors and with six dwarf coconut accessions in three cycles of production using 19 descriptors of fruits and 11 leave descriptors. The data obtained were subjected to univariate and multivariate analyses using the software GENES and Selegem. Among the accessions of tall coconuts the most dissimilar ones considering the morphoagronomical characters were Gigante-de-Rotuma and Gigante-do-Oeste Africano and they can be indicated as parents for coconut breeding programs. It was also found a great genetic variability among the coconut dwarf accessions of the ICG-LAC Bank, and this divergence was found to be consistent in the individual and joint analyses, including an analysis of maximum likelihood restricted (REML) taking into account a sample of morphological descriptors. The 14 coconut accessions (eight tall and six dwarfs) were used to perform a chemical evaluation of oil and their components in a cycle of crop production in two different field trials. It was found that some dwarf coconut accessions presented values of oil content similar to coconut tall accessions. Therefore, the best accessions can be exploited for coconut water as well as for production of oil and they can be selected as potential superior parents to be used in coconut breeding program.